Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 14: Partial Derivatives - Section 14.1 - Functions of Several Variables - Exercises 14.1 - Page 788: 61


$2=\sqrt {x-y}-\ln z$

Work Step by Step

Here, the level curve for $f(x,y,z)=\sqrt {x-y}-\ln z$ has the form of $c=\sqrt {x-y}-\ln z$ Also, $x=3,y=-1,z=1$ This implies that $c=\sqrt {3-(-1)}-\ln (1)$ or, $c=2 $ Hence, $c=\sqrt {x-y}-\ln z \implies 2=\sqrt {x-y}-\ln z$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.